2021
DOI: 10.3390/cancers13112655
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Instability in Acute Myeloid Leukemia

Abstract: Chromosomal instability (CIN), the increasing rate in which cells acquire new chromosomal alterations, is one of the hallmarks of cancer. Many studies highlighted CIN as an important mechanism in the origin, progression, and relapse of acute myeloid leukemia (AML). The ambivalent feature of CIN as a cancer-promoting or cancer-suppressing mechanism might explain the prognostic variability. The latter, however, is described in very few studies. This review highlights the important CIN mechanisms in AML, showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 269 publications
(270 reference statements)
1
13
0
Order By: Relevance
“…Genomic instability is a hallmark of AML pathogenesis. Different chromosomal translocations were acquired during AML development and are considered an important tool in the anticipation of patients' treatment outcomes and prognosis 43 . One study showed that H3K9 methylation induced by EHMT2/G9a was enriched in genomic blocks that contain proto‐oncogenes and sites of chromosomal translocations in AML.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic instability is a hallmark of AML pathogenesis. Different chromosomal translocations were acquired during AML development and are considered an important tool in the anticipation of patients' treatment outcomes and prognosis 43 . One study showed that H3K9 methylation induced by EHMT2/G9a was enriched in genomic blocks that contain proto‐oncogenes and sites of chromosomal translocations in AML.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal instability creates cytogenetic diversity and is a common feature in hematological malignancies, especially in all types of acute myeloid leukemia (de novo AML, secondary AML, and therapy-related AML), increasing the risk of the disease [15]. Considering the abnormal result of the examination of the patient's sister, we advised careful monitoring for hematological abnormalities and thorough examination if any alterations occur.…”
Section: Discussionmentioning
confidence: 99%
“…Metaphase cells from short-term 24 h unstimulated cultures were examined. Bone marrow cytogenetic testing exhibited complex karyotype described according to the International System of Human Cytogenomic Nomenclature (ISCN) 2020 as 46,XX,t(4;8)(q32;q13), t(4;11)(q23;p15),del(5)(q15q34) [15]/47,XX,sl,+der(4)t(4;8)(q?32;q?13). FISH test has confirmed interstitial deletion of the long arm of chromosome 5: nuc ish(D5S23,D5S721x2), (EGR1x1)[180/200], (D5S23,D5S721x2),(CSF1Rx1)[180/200] (Figure 1).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Polo-like kinase 4 (PLK4) plays a crucial role in controlling centriole duplication, and its deregulation causes centrosome number abnormalities, mitotic defects, chromosomal instability, and, consequently, tumorigenesis [56]. Genomic instability and cell cycle deregulation favor the rapid proliferation and clonal expansion of cells harboring oncogenic DNA alterations in AML [57][58][59]. The upregulation of hub genes controlling these processes reflects the tendency of hematopoietic precursor cells in bone marrow to accumulate DNA lesions and increase their proliferation rate at the expense of normal hemopoiesis, resulting in bone marrow failure.…”
Section: Discussionmentioning
confidence: 99%